Influence of interface components on the street level - Adeb Qaid Ahmed Al-Ameri, 1979-; Dilshan Remaz Ossen, supervisor; Fakulti Alam Bina (2010)
Thesis (Sarjana Sains (Rekabentuk Bandar)) - Universiti Teknologi Malaysia, 2010